EMA Review of Daratumumab (Darzalex) for the Treatment of Adult Patients Newly Diagnosed with Multiple Myeloma. (16th October 2020) - Michaleas, Sotirios; Penninga, Elisabeth; Hovgaard, Doris; Dalseg, Anne‐Marie; Rosso, Aldana; Sarac, Sinan B.; Jimenez, Jorge Camarero; Fernández, Lucia López‐Anglada; Fernández, Carolina Prieto; Mangas‐SanJuan, Victor; Garcia, Isabel; Payares‐Herrera, Concepcion; et al.
Abstract: : The use of daratumumab in combination with established regimens for the treatment of newly diagnosed multiple myeloma has recently been authorized by the European Medicines Agency based on results from three separate phase III randomized, active controlled, open‐label studies that have confirmed enhanced efficacy and tolerability in both transplant‐ineligible (MMY3008 and MMY3007) and transplant‐eligible (MMY3006) patients, without compromising transplant ability. Trial MMY3008 showed an improvement in progression‐free survival (PFS) when daratumumab was added to lenalidomide and dexamethasone compared with lenalidomide and dexamethasone; the median PFS had not been reached in the daratumumab arm and was 31.9 months in the control arm (hazard ratio [HR], 0.56; 95% confidence interval [CI], 0.43–0.73; p < .0001). Trial MMY3007 showed an improvement in PFS when daratumumab was added to bortezomib, melphalan, and prednisone compared with bortezomib, melphalan, and prednisone; PFS had not been reached in the daratumumab arm and was 18.1 months in the control arm (HR, 0.5; 95% CI, 0.38–0.65; p < .0001). In trial MMY3006, daratumumab added to bortezomib, thalidomide, and dexamethasone was compared with bortezomib, thalidomide, and dexamethasone as induction and consolidation treatment prior to autologous stem cell transplant. The stringent complete response rate at day 100 after transplant in the daratumumab group was 29% compared with 20% in the control group (odds ratio, 1.60; 1.21–2.12 95% CI; p = .0010). Overall adverse events were manageable, with an increased rate of neutropenia and infections in the daratumumab arms. Regulatory assessment of efficacy and safety results from trials MMY3006, MMY3007, and MMY3008 confirmed a positive benefit‐risk ratio leading to an approval of the extensions of indication. Implications for Practice: A set of extensions of indication was recently approved for daratumumab (Darzalex) in the setting of newly diagnosed multiple myeloma in combination with established regimens. Results of the MMY3006, MMY3007, and MMY3008 trials have shown enhanced efficacy and a favorable side effect profile of several daratumumab‐based combinations in patients both ineligible and eligible for transplant, without compromising transplant ability. The combinations of daratumumab with either lenalidomide and low‐dose dexamethasone or bortezomib, melphalan, and prednisone were approved for transplant‐ineligible patients. The combination of daratumumab with bortezomib, thalidomide, and dexamethasone was approved for transplant‐eligible patients. These combinations are expected to improve the survival outlook for patients with multiple myeloma, without an unacceptable risk of increase in adverse events, and updated information on progression‐free survival and overall survival is expected from the above trials. Abstract : This report outlines the regulatory steps taken for the approval of extensions of indication of daratumumab for the treatment of adult patients with newly diagnosed multiple myeloma who are ineligible for autologous stem cell transplant. The pivotal clinical data submitted and EMA review of the benefit‐risk assessment are summarized.